Vanilla cardinalis (Orchidaceae, Vanilloideae), a new red-lipped species from southern Vietnam - Averyanov, Leonid V.; Nuraliev, Maxim S.; Thai, Tran Huy; Maisak, Tatiana V.; Popov, Eugene S.; Lyskov, Dmitry F.; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P. (Phytotaxa, 2022)
A new species, Vanilla cardinalis (Orchidaceae, Vanilloideae) discovered in southern Vietnam (Phu Yen Province, Song Hinh District) is described and illustrated. Data on ecology, phenology, distribution, and estimated IUCN Red List conservation status of the new species are provided. Differences of V. cardinalis from its morphologically similar congeners are briefly discussed. Additionally, a checklist of the genus Vanilla and the morphologically similar Miguelia in Vietnam is presented.